When Is HILO Low? Price Image Formation Based on Frequency versus Depth Pricing Strategies - Sheehan, Daniel; Hamilton, Ryan; Chellappa, Ramnath K (Journal of Consumer Research, 2022)
Abstract One of the prominent pricing decisions a retailer can make is its choice of pricing strategy. Previous research investigating consumers’ responses to stores with frequent, shallow price advantages relative to competitors (a frequency strategy) versus stores with infrequent, deep price advantages (a depth strategy) was all conducted by allowing people to simultaneously view prices from multiple stores, a setting that emphasized across-store comparisons. The present research finds that when a store’s prices are evaluated separately, as opposed to simultaneously across stores, many of the prominent findings of previous research are reversed. The authors demonstrate that without simultaneous comparisons across stores, consumers shift from using across-store prices as reference points to using within-category reference prices. As a result of this shift, deep price advantages are easier to evaluate than frequent price advantages, and therefore more influential on consumers’ formation of price image. When stores are evaluated separately, the result is most often a depth advantage, where stores with a HILO pricing strategy are evaluated as having a lower price image than EDLP stores, even when the average prices are the same. These results cannot be explained by prior work related to frequency and depth pricing strategies that relied on across-store comparisons.